2020
DOI: 10.1111/1749-4877.12482
|View full text |Cite
|
Sign up to set email alerts
|

Elusive cats in our backyards: persistence of the North Chinese leopard (Panthera pardus japonensis) in a human‐dominated landscape in central China

Abstract: The North Chinese leopard (Panthera pardus japonensis), the least‐known big cat, disappeared in most historical range for decades, following the development of modern civilization. Unfortunately, we have scarce knowledge about the status of this big cat so far, apart from anecdotal reports. In this study, we investigated density, distribution, and habitat use of the leopard, the apex predator, in a complex forest landscape in the Loess Plateau. We used a camera‐trapping network to obtain population estimates f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…There are reports that the habitat of the North China leopard is facing widespread shrinkage and destruction [1]. However, the population density of North China leopards in the study area is relatively high [24]. In addition, according to the unpublished gene exchange study of the North China leopard population in the research group, research found that the North China leopard in the study area had serious inbreeding pressure.…”
Section: Population Size and Density Distribution Of North China Leopardmentioning
confidence: 85%
“…There are reports that the habitat of the North China leopard is facing widespread shrinkage and destruction [1]. However, the population density of North China leopards in the study area is relatively high [24]. In addition, according to the unpublished gene exchange study of the North China leopard population in the research group, research found that the North China leopard in the study area had serious inbreeding pressure.…”
Section: Population Size and Density Distribution Of North China Leopardmentioning
confidence: 85%
“…Other studies also revealed that leopards avoided human settlements, and wild boar are considered a pest animal or otherwise are negatively perceived by people including because of crop damage (Zhou et al, 2021 ; Zhu et al, 2021 ); wild boar may, therefore, adopt spatiotemporal avoidance behaviors. However, species interactions and activities may be context specific as others have found that ungulate herbivores during daytime overlap with humans on foot in different habitats (Yang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…While we expect that leopards move throughout the fragmented landscape by using high elevation corridors, these highest areas also may provide suitable habitat and maximum hunting opportunity for ungulates or medium‐sized prey (Pu et al, 2019 ); the relationships with elevation were consistent across leopards and two of three prey species studied, while the leopards and roe deer had similar use of areas near to secondary roads during the daytime. (Yang et al, 2021 ; Zhu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations